Penerapan Nilai-Nilai Pendidikan Akhlak Terpuji Santri Putri Kelas Sifir C dalam Mengkaji Kitab Alala di Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan - Liza Nurazizah; Weni Kurniawati; Finy Muslihatuzzahro (Departement of Mathematics Education, 2024)
Many students still do not respect their elders, are dishonest when friends do not study the Koran on the grounds of pretending to be sick and are impatient when memorizing and choose not to study the Koran. Even though they have studied the Alala book, their behavior is still not good towards the ustadz/ustadzah. In response to this problem, it is necessary to apply a more appropriate method, one of which is the habituation method. The habituation method is a very important educational method, especially for children. Because this method gets them used to good things such as getting used to shaking hands with their fathers and mothers. This study aims to determine the Implementation, Advantages and Obstacles of the Implementation of the Values ​​of Praiseworthy Moral Education for Female Students of Class Sifir C in Studying the Alala Book at the Hidayatul Mubtadiin Jati Agung Islamic Boarding School in the 2023/2024 Academic Year. Data analysis techniques using 3 stages, namely, data reduction, data presentation, and drawing conclusions. This research is a Qualitative Research, the type of this research is descriptive qualitative with the research subjects of 3 Ustadzah and 2 female students of class sifir c of the Hidayatul Mubtadiin Jati Agung Islamic Boarding School. The data collection technique in this study was through observation, interviews, and documentation. The results of the study showed that the application of commendable morals in studying the alala book consisted of 3 activity sessions, namely the Opening Stage, the Ustadzah and students read hadloroh together followed by reading Surah Alfatihah. The second is the delivery of material using classical techniques and memorizing the verses. And the third activity is the Closing Stage. The advantage of the Application of commendable morals in studying the alala book is that students know more about good manners towards teachers. The lecture method used is very easy to absorb by students because the verses are very easy to memorize and not too long. Obstacles to the application of commendable morals in studying the Alala book are the level of ability and enthusiasm of each student is different from other students, lack of concentration of students during learning.